2011
DOI: 10.1017/s0022215111001095
|View full text |Cite
|
Sign up to set email alerts
|

Is it oncologically safe to leave the ipsilateral submandibular gland during neck dissection for head and neck squamous cell carcinoma?

Abstract: Submandibular gland metastasis from head and neck primary squamous cell carcinoma is extremely rare. Preservation of the ipsilateral submandibular gland during neck dissection is oncologically safe, except in patients with prior surgery or radiotherapy, or a primary tumour in close relation to the gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…3 Studies have reported the prevalence of submandibular gland involvement by head and neck carcinoma to range from 0.9% to 5.3%. [4][5][6][7][8] Submandibular gland involvement is most commonly secondary to direct extension from level I nodal disease or direct extension from a primary oral cavity tumor. As a result, the necessity of submandibular gland removal during neck dissection has been questioned.…”
Section: Introductionmentioning
confidence: 99%
“…3 Studies have reported the prevalence of submandibular gland involvement by head and neck carcinoma to range from 0.9% to 5.3%. [4][5][6][7][8] Submandibular gland involvement is most commonly secondary to direct extension from level I nodal disease or direct extension from a primary oral cavity tumor. As a result, the necessity of submandibular gland removal during neck dissection has been questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have reported metastasis to submandibular gland from an index tumor in head and neck is either very rare or never found [13][14][15][16]. Fibrous capsule surrounding the submandibular gland provides an effective barrier to the spread of squamous cell carcinoma, even when the gland is compressed by bulky metastatic disease [17].…”
Section: Discussionmentioning
confidence: 66%
“…Based on their study findings, the authors thought that it might be feasible and safe to preserve an oncologically sound submandibular gland during neck dissection in patients with early-stage oral cancer [18]. Other studies revealed similar results, demonstrating that submandibular gland metastasis from head and neck primary squamous cell carcinoma was extremely rare and that direct invasion as a primary mechanism of metastasis led to most of the metastases [6, 7, 9, 10]. These studies concluded that preservation of the submandibular gland might be oncologically safe and feasible unless there was evidence of direct invasion of the gland or close proximity of the cancer to it.…”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of submandibular glands in oral cavity and oropharyngeal cancers is quite rare, especially in early oral cancers [5, 6]. Additionally, the existence of intraglandular lymph nodes within submandibular glands continues to be debated [7, 8]. Studies have demonstrated that preservation of the submandibular gland during neck dissection is oncologically safe in patients with early oral cancers unless the primary tumor or metastatic regional lymphadenopathy is adherent to the gland [9, 10].…”
Section: Introductionmentioning
confidence: 99%